The Influence of Organizational Culture on the Level of Innovation in Manufacturing Companies - Zhang Li; Yang Xiang; Sun Wei (Yayasan Adra Karima Hubbi, 2024)
This study examines the influence of organizational culture on the level of innovation in manufacturing companies. Organizational culture plays a crucial role in shaping the behavior of employees and influencing how companies adapt to changes and foster innovation. Despite the growing importance of innovation in maintaining competitiveness in the manufacturing sector, the relationship between organizational culture and innovation has not been fully explored in this context. This research aims to investigate how different dimensions of organizational culture—such as support for risk-taking, communication practices, and employee involvement—affect innovation outcomes in manufacturing firms. A quantitative research design was employed, using surveys distributed to employees in various manufacturing companies across different regions. The survey data were analyzed using statistical methods, including regression analysis, to determine the correlation between organizational culture and innovation levels. The findings indicate that a strong, innovation-supportive organizational culture significantly enhances the innovation capacity of manufacturing companies. Specifically, companies with cultures that promote open communication and risk-taking showed higher levels of innovative output. The study concludes that fostering a culture that values creativity, risk-taking, and collaboration can significantly improve innovation outcomes in manufacturing companies. Future research should further explore the role of leadership in shaping organizational culture and driving innovation within this sector.